Hereditary sideroblastic anaemia and ataxia: an X linked recessive disorder. Issue 4 (August 1985) - Pagon, R A; Bird, T D; Detter, J C; Pierce, I
Abstract : We report two families in which a non-progressive spinocerebellar syndrome and a sideroblastic anaemia are segregating together in an X linked recessive fashion. Four males in two generations of one family and a fifth male from an unrelated family had both conditions. Both the sideroblastic anaemia and the spinocerebellar syndrome differ from those which have previously been reported to be inherited in an X linked recessive manner. The association of these two clinically distinct disorders in two unrelated families suggests that they are either two closely linked loci which have undergone simultaneous mutation or pleiotropic effects of an altered allele at a single locus. All the heterozygous women had normal neurological examinations and normal haematocrits and red cell indices. Some had ring sideroblasts on bone marrow examination, a dimorphic peripheral blood smear, and raised serum free erythrocyte protoporphyrin, suggesting that a proportion of heterozygotes can be detected by appropriate haematological studies.